Studies on the estimation of the hygienic condition of frozen broiler chickens. - Van Schothorst, M. (Cambridge University Press, 1976)
Various sampling techniques to determine the aerobic, E. coli and Enterobacteriaceae counts and to detect the presence of salmonellas were compared. As a simple method for the detection of salmonellas a modified Surkeiwicz procedure using both drip and rinse water is advocated. To evaluate hygiene during processing, determination of the number of Enterobacteriaceae in pieces of skin from the ventral, lateral and breast region is preferred.